Evaluation of Moringa (Moringa oleifera Lamp) powders and seed aqueous extract for the control of Khapra Beetle (Trogoderma granarium Everts) - Mohammed, Dr. Ashwag Ahmed; kheir, Dr Seif Eldin Mohamed; Ismeal, Elhadi Musa (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2017)
The study investigated the comparative efficacy of Moringa ( Moringa oleifera Lamp) powders from different plant parts (leaf, flower, seed and branch) on the suppression of khapra beetle (Trogoderma granarium (Everts.) (the 3 rd larval instar) damage in sorghum grains. Three rates 1%, 2.5%, and 5% w/w of the plant powders were used under laboratory conditions. The experiment was laid out in Completely Randomized Design (CRD) of four treatments. Each treatment was replicated four times .Ten larvae of khapra beetle were introduced into each petridish . Mortality of khapra beetle larvae was recorded after 1, 3, 7 and 30 days. Result indicated that Moringa seeds powder was more effective in causing khapra beetle larvae mortality. The sorghum grains treated with Moringa seed powder gave a high range of 7.5- 2.5% larvae mortality compared to the low range of 2.5- 0.0% recorded in sorghum grains treated with Moringa leaves powder at 1 day. A progressive increase in mortality ranging from 15.0-42.5% in sorghum grains treated with Moringa seed powder and 12.5- 22.5% sorghum grains treated with Moringa leaves powder were achieved at 5% rate after 3 and 30 days respectively. The LC50 and LC90 revealed that Moringa seed powder to be the most effective one. Also result revealed that Moringa seed powder is more effective than seed aqueous extract in the control of khapra beetle larvae. Out of the four powder parts of the Moringa investigated , seed powder was the most effective biopesticide and thus will be recommended